Kreacja i przesunięcie handlu w procesie rozszerzenia Unii Europejskiej ze szczególnym uwzględnieniem Polski - Dieckheuer, Gustav; Mlakar, Marcel; Stemmann, Ute (Trade Creation and Trade Diversion by EU Enlargement with Special Reference to Poland, 2005)
Our aim is to analyse some macroeconomic aspects of the impact of an EU enlargement on trade between the EU, new member countries (NMCs) and the rest of the world (ROW / also referred to as third countries TCs). To capture the effects of integration due to the removal of trade barriers we present a general theoretical framework and contrast those results with some empirical evidence for the special situation of Poland, which is - concerning absolute levels of population and GDP - the most important NMC25. The paper is organized as follows: in part 2 we begin with some introductory remarks and data concerning changes of trade flows during the years after starting the transformation process in Eastern Europe. To identify the effects of an elimination of trade barriers between current and new UE members on direction and volume of trade a theoretical analysis is presented in part 3. We develop two different models - at first a traditional model of trade creation and trade diversion caused by economic integration and secondly a model of broader interdependence between export and import markets of old and new members of an integration area as well as ROW-counties. Part 4 presents some empirical facts about Poland's foreign trade and its current restrictions, showing that most of the theoretically predicted effects have already been realized. Part 5 is - along with the theoretical findings - the basis for the assessment of prospects for trade flows between Poland and other countries after Poland's accession to the EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 15-34